2005
DOI: 10.1679/aohc.68.171
|View full text |Cite
|
Sign up to set email alerts
|

The presence of ferric and ferrous iron in the nonheme iron store of resident macrophages in different tissues and organs: histochemical demonstrations by the perfusion-Perls and -Turnbull methods in the rat

Abstract: We previously developed the highly sensitive perfusion-Perls and -Turnbull methods to visualize nonheme ferric (Fe (III)) and ferrous (Fe (II)) iron, respectively. The present study used these methods to investigate the possible presence of nonheme iron in the redox (ferric/ferrous) state in the noneheme iron store (phagolysosomes and siderosomes) of resident macrophages in the rat. The perfusion-Perls and -Turnbull methods at pH 0.6 supplemented by DAB intensification intensely stained resident macrophages of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…1E). We identified no spinning cells in the spleen indicating that the iron-rich macrophages (which are abundant in this tissue) do not spin (29). To ascertain whether the observed spinning cells comprised a single morphological class, we analyzed their appearance using both transmitted light and fluorescent imaging staining with the membrane marker FM1-43 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1E). We identified no spinning cells in the spleen indicating that the iron-rich macrophages (which are abundant in this tissue) do not spin (29). To ascertain whether the observed spinning cells comprised a single morphological class, we analyzed their appearance using both transmitted light and fluorescent imaging staining with the membrane marker FM1-43 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Wild-type and sla mice were perfused with the perfusion-Perl's method, and spinal cords were prepared for electron microscopy according to a previously described protocol (Meguro et al, 2005). In brief, mice were first perfused with 0.1 M phosphate buffer, pH 7.4, containing heparin (10 U/ml), then with 4% paraformaldehyde and 1.5% glutaraldehyde in 0.1 M phosphate buffer, pH 7.4, followed by 4% paraformaldehyde, 1% glutaraldehyde, and 1% potassium ferrocyanide in distilled H 2 O, pH 1.0.…”
Section: Methodsmentioning
confidence: 99%
“…The DAB-enhanced histochemical iron stains described by Smith (Smith et al 1997) and LeVine (LeVine 1991) have been reported to label AD plaques. The Meguro method (Meguro et al 2007) has not been described in human brain tissue or animal models of AD but has been widely used in other organs in rats, mice, and monkeys (Meguro et al 2005;Meguro et al 2007;Freret et al 2008;Iwatsuki et al 2008;Meguro et al 2008;Butt et al 2010;Winter et al 2010;Butt et al 2011;Shpyleva et al 2011).…”
Section: +mentioning
confidence: 99%